The Institutionalization of Indonesian SHIISM and the Emergence of a New Wave - Muhammad Baqir Idrus Alatas; Dede Syarif (Green Publisher Indonesia, 2026)
Studies of Shia Islam in Indonesia have generally focused on the role of individual figures, such as scholars, intellectuals, and campus activists, as the main drivers of the community. This approach tends to emphasize the development of Shia Islam through individuals. This study aims to identify the emergence and development of Shia Islam in Indonesia through processes of institutionalization across various institutions, as well as to explain the role of formal organizations—especially Pandu Ahlulbait Indonesia—in forming a more collective, systematic, and sustainable pattern of Shia community movements. This study uses a qualitative approach with semi-structured interviews and document analysis. This method is used to trace the processes, factors, and consequences of the institutionalization of Shia communities across various organizational institutions that are developing in Indonesia. The results of the study show that the institutionalization of the Shia community marks the emergence of a new wave of Shia development in Indonesia. This is indicated by the strengthening of formal organizations, especially through autonomous institutions such as Pandu Ahlulbait Indonesia. The organization actively involves the younger generation and women, utilizes digital technology, and develops a multi-issue da'wah orientation, thereby forming a more collective and systematic movement. This study confirms that institutionalization is an adaptive strategy of the Shia community in responding to contemporary socio-religious dynamics in Indonesia.